2022
DOI: 10.1021/acs.chemrev.2c00426
|View full text |Cite
|
Sign up to set email alerts
|

Design of the Synergistic Rectifying Interfaces in Mott–Schottky Catalysts

Abstract: The functions of interfacial synergy in heterojunction catalysts are diverse and powerful, providing a route to solve many difficulties in energy conversion and organic synthesis. Among heterojunction-based catalysts, the Mott–Schottky catalysts composed of a metal–semiconductor heterojunction with predictable and designable interfacial synergy are rising stars of next-generation catalysts. We review the concept of Mott–Schottky catalysts and discuss their applications in various realms of catalysis. In partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(70 citation statements)
references
References 266 publications
1
69
0
Order By: Relevance
“…As shown in the Fig. 7 a, the positive slope proves the n -type semiconducting [71] , [72] nature of the Ti 2 SnC MAX phase. Based on the intercept obtained by aligning the linear portion of the M−S plot to the potential axis [73] , the catalyst’s flat band potential is determined as −0.72 V vs SCE.…”
Section: Resultsmentioning
confidence: 57%
“…As shown in the Fig. 7 a, the positive slope proves the n -type semiconducting [71] , [72] nature of the Ti 2 SnC MAX phase. Based on the intercept obtained by aligning the linear portion of the M−S plot to the potential axis [73] , the catalyst’s flat band potential is determined as −0.72 V vs SCE.…”
Section: Resultsmentioning
confidence: 57%
“…The images showed that the metallic Pd nanoparticles were successfully deposited with good distribution on the surface of GaN (Figures S2 and S3). Previous reports have shown that the deposition of high work function metal Pd on GaN could form the Schottky junction, which is critical for charge transfer. , These metal–semiconductor interfaces can significantly increase the lifetime of electron–hole pairs, enhancing the catalytic activity. Figure a displays the photoluminescence spectra of commercial GaN and the designed 3 wt % Pd/GaN. The intensity of the photoluminescence emission decreases as Pd nanoparticles are deposited on the surface of GaN.…”
Section: Resultsmentioning
confidence: 99%
“…Frontiers in Chemistry frontiersin.org 2020; Žerjav et al, 2021). Schottky proposed a metal-semiconductor contact barrier model under ideal conditions that ignores the interface state, so it is called the Schottky barrier (Xu et al, 2023). Catalysts with Schottky barrier are generally of strong capacity to improve the separation of electron hole pairs, thereby exhibiting superior catalytic performance.…”
Section: Tiomentioning
confidence: 99%